Zen Serigrafia: trinta anos de permanência no processo permeográfico - Aminger, Andréa Franco (2018)
The present dissertation has, as object of study, the historical report of the carioca Zen Serigrafia, specialized in the permeographic process. Since its foundation in 1988, these printers has remained until the present day with the same type of printing, completing, by the end of 2018, thirty years of existence and permanence with this process. For the elaboration of this historical record, interviews with the owners and with some of their main graphic design clients were used. We also present how these printers relate to the Creative Economy, because we understand that Design is one of its areas. Since its inception, it has maintained close service to its customers, being also related to a tradition, thus maintaining itself for thirty years, always with the same type of printing process, while most of the printers that began in this process shifted to the digital medium, changing both in relation to the service and the type of printing. As a result of the interviews with the graphic design clients, the relationship of these printers and the luxury market was also identified, although the owners did not yet recognize this path. Thinking about the permanence of these printers and this process in the future, we can see the development of the approach with the young designers, because these new professionals are now further distant. We verified that this could be due to the fact that these printers do not develop a good promotional material, despite the social media. We have, as a result of this professional master's degree, developed an exhibition that presents the history of these printers until then, with some graphic designers´ work on show. The proposal of this exhibition is that it happens in a cultural center located within a university that has, in its curriculum, courses related to the area of graphic design, thus creating the possibility that young designers know and become interested on this subject, because we can not forget that they are the main responsible for the continuity of this story